Metode Demonstrasi Dalam Upaya Miningkatkan Proses Belajar Dan Hasil Belajar Bahasa Indonesia Sekolah Dasar Kelas V - Martha Mbindi (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
The success of learning objectives is determined by many factors including the factor of the teacher in implementing the teaching and learning process, because the teacher can directly influence, foster and improve student intelligence and skills. To overcome the above problems and to achieve educational goals to the fullest, the role of the teacher is very important and it is hoped that the teacher has a way / model of teaching that is good and able to choose the right learning model and in accordance with the concepts of the subject to be delivered. The problems that want to be studied in this study are: (a) How is the improvement of student learning achievement by applying the demonstration learning method? (b) What is the effect of demonstration learning methods on student motivation?